Dampak Kemiskinan Terhadap Sarana dan Prasarana Pendidikan - Hafizi, M. Zainul; Pratama, Selvina; Putri, Kezya Meylani Fernanda; Panamuan, Fortunata Blandina; Manalu, Esteritta; Rahma, Fitria Ghaida Nur; Ananda, Dhea (Yayasan Alpatih Harapan Semesta, 2024)
Poverty remains one of the major factors hindering the equal distribution of education quality in Indonesia. Economic limitations directly affect the availability of school facilities, ranging from infrastructure, laboratories, and libraries to access to digital technology. This study employs a descriptive qualitative method and literature review to analyze the impact of poverty on educational facilities. The findings reveal that schools in impoverished areas often lack adequate classrooms, functional laboratories, sufficient book collections, and digital resources to support learning. Such conditions not only lower the quality of education but also widen the gap between wealthy and underprivileged regions. Addressing this issue requires collaborative efforts from the government, private sector, and society through initiatives such as operational assistance programs, school revitalization, and CSR support. These efforts are expected to foster a more inclusive, equitable, and high-quality education system for all students across Indonesia